Targeted next generation sequencing and identification of risk factors in World Health Organization defined atypical chronic myeloid leukemia. Issue 6 (29th April 2017) - Patnaik, Mrinal M.; Barraco, Daniela; Lasho, Terra L.; Finke, Christy M.; Reichard, Kaaren; Hoversten, Katherine P.; Ketterling, Rhett P.; Gangat, Naseema; Tefferi, Ayalew
Abstract: Atypical chronic myeloid leukemia (aCML) is an aggressive myeloid neoplasm with overlapping features of myelodysplastic syndromes (prominent granulocytic dysplasia) and myeloproliferative neoplasms (neutrophilic leukocytosis). We studied 25 molecularly‐annotated and World Health Organization defined aCML patients; median age 70 years, 84% males. Cytogenetic abnormalities were seen in 36% and gene mutations in 100%. Mutational frequencies were, ASXL1 28%, TET2 16%, NRAS 16%, SETBP1 12%, RUNX1 12%, ETNK1 8%, and PTPN11 4%. Fifteen patients (60%) had >1 mutation, while 9 (36%) had ≥3. The median overall survival (OS) was 10.8 months and at last follow up (median 11 months), 17 (68%) deaths and 2 (8%) leukemic transformations were documented. On univariate analysis, survival was adversely impacted by advanced age ( P  = .02), low hemoglobin ( P  = .01), red blood cell transfusion dependence ( P  = .03), high white blood cell count ( P  = .02), TET2 ( P  = .03), NRAS ( P  = .04), PTPN11 ( P  = .02) mutations and the presence of ≥3 gene mutations ( P  = .006); ASXL1, SETBP1, and ETNK1 mutations did not impact OS. In multivariable analysis, advanced age ( P  = .003) [age >67: HR 10.1, 95% CI 1.3‐119], low hemoglobin ( P  = .008) [HB< 10 gm/dL: HR 8.2, 95% CI 1.6‐23.2] and TET2 mutations ( P  = .01) [HR 8.8, 95% CI 1.6‐47.7] retained prognostic significance. We then used age >67 years, hemoglobin <10 gm/dL and the presence of TET2 mutations (each counted as one risk factor) to create a hazard ratio weighted prognostic model; effectively stratifying patients into two risk categories, low (0‐1 risk factor) and high (≥2 risk factors), with median OS of 18 and 7 months, respectively.